If it's not what You are looking for type in the equation solver your own equation and let us solve it.
n-5n-(-n)=0
We simplify the equation to the form, which is simple to understand
n-5n-(-n)=0
Remove unnecessary parentheses
n-5n+1n=0
We move all terms containing n to the left and all other terms to the right.
+1n-5n+1n=0
We simplify left and right side of the equation.
-3n=0
We divide both sides of the equation by -3 to get n.
n=-0
| 12y=64+4y | | 10r-11=8r+19 | | 90=50/x | | x^2+4x-2=-2 | | .60k+.70=.73k+-.40 | | 2(x-5)2+4=x | | .90=50/x | | Y=0.33x+1 | | 4y-18=2y+14 | | (x+5)+22=90 | | 8y-6=6y+20 | | 2x+8=4x+-2 | | 3x(x-4)=(x-10)(x-2) | | 6a^2b+7ab-3b= | | 11t-14=4t+7 | | -0.5x^2+4.5x=0 | | 13t-13=8t+2 | | -12+0.1= | | 27.98(28)=-1.891*28+96.053 | | 14t-6=9t+19 | | -2(a+3)-a=10 | | 10p+120=x | | X+50+30x+2x+10=180 | | 1.2x+37=2.2x+-4.5 | | f(f+6)=23 | | 13s-13=3s+17 | | -7(z-9)-(1-3z)=-5z | | 11.25+0.125=x | | 1/3n•4 | | (x-2)(y+4)=6 | | w=p(w-z) | | 13+9-11a= |